Poetry into song performance and analysis of lieder - Stein, Deborah J. (Deborah Jane) (Oxford University Press, 1996)
When Franz Schubert put Goethe's poem "Gretchen am Spinnrade" to music in 1814, he created a musical form that has captivated audiences ever since. In Poetry into Song, Deborah Stein and Robert Spillman challenge readers to seek a richer, more imaginative understanding of Lied - the nineteenth-century German art song. Written for students of voice, piano, and theory and for all singers and accompanists, Poetry into Song establishes a framework for the analysis of song based on a process of performing, listening, analyzing, and performing again. This unique approach emphasizes the reciprocal interaction between performance and analysis. Focusing on the masterworks, Poetry into Song features numerous poetic texts, as well as a core repertory of songs. Examples throughout the text demonstrate points, and end of chapter questions reinforce concepts and encourage directed analysis. While numerous books have been written on Lieder and German Romantic poetry, Poetry into Song is the first to combine performance, musical analysis, textual analysis, and the interrelation between poetry and music in a truly systematic, thorough way.